Gastric Mucosa-Associated Lymphoid Tissue Lymphomas Diagnosed by Jumbo Biopsy Using Endoscopic Submucosal Dissection: A Case Report - Han, Jian; Wang, Jun; Xie, Hua-ping (Frontiers in Medicine, 2021)
The stomach is the most common primary site of mucosa-associated lymphoid tissue (MALT) lymphoma, and sometimes the histopathological diagnosis is particularly difficult. An endoscopic forceps biopsy is the primary diagnostic test, but false negative results are very common. Therefore, a jumbo biopsy is essential for accurate diagnosis of clinically suspected cases. Here we diagnosed two cases of gastric MALT lymphomas using endoscopic submucosal dissection (ESD). The first patient was suspected of gastric lymphoma at the first endoscopic forceps biopsy, but the second endoscopic forceps biopsy showed chronic inflammation. The second patient was also firstly diagnosed with chronic inflammation by endoscopic forceps biopsy. Both cases were finally confirmed with the diagnosis of gastric MALT lymphoma by jumbo biopsy using ESD. The application of ESD can provide a new diagnostic strategy for clinically suspicious cases of gastric MALT lymphoma with negative endoscopic forceps biopsy.